2022
DOI: 10.3389/fneur.2021.831035
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Allodynia in Migraine: A Narrative Review

Abstract: ObjectiveIn the present work, we conduct a narrative review of the most relevant literature on cutaneous allodynia (CA) in migraine.BackgroundCA is regarded as the perception of pain in response to non-noxious skin stimulation. The number of research studies relating to CA and migraine has increased strikingly over the last few decades. Therefore, the clinician treating migraine patients must recognize this common symptom and have up-to-date knowledge of its importance from the pathophysiological, diagnostic, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 85 publications
(88 reference statements)
1
20
0
Order By: Relevance
“…CA is a condition defined as perceptions of pain elicited by the application of nonpainful stimuli to normal skin; it has been observed in 60% of patients with migraine 59 and is even more prevalent in patients with chronic migraine (up to 90%). 60 The CS of trigeminovascular neurons has been implicated in the development of CA.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…CA is a condition defined as perceptions of pain elicited by the application of nonpainful stimuli to normal skin; it has been observed in 60% of patients with migraine 59 and is even more prevalent in patients with chronic migraine (up to 90%). 60 The CS of trigeminovascular neurons has been implicated in the development of CA.…”
Section: Methodsmentioning
confidence: 99%
“…Other risk factors for CA include acute medication overuse and early age of migraine onset. 59 Longitudinal data over 2 years showed that CA is an independent risk factor for migraine chronification. 62 A study of resting-state functional connectivity showed that compared to migraine patients without ictal CA, migraine patients with ictal CA showed stronger functional connectivity of the periaqueductal gray and nucleus cuneiformis to other brainstem, thalamic, insular and cerebellar regions that participate in discriminative pain processing as well as higher order pain-associated regions, such as the frontal and temporal cortices.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The nature of this predisposition to migraine pain is probably multifactorial and polygenic and it can vary between different individuals and within the same individual over time. It could be linked to the multiple peculiarities of the “migraine brain” [ 81 ], to a lower allodynic threshold [ 82 ], might be modulated by estrogen fluctuations in female sex, and can explain the observation that the CGRP or PACAP induce a migraine attack only in migraine patients [ 14 , 15 ]. In this perspective, migraine remains a “primary” disease that afflicts a minority of the individuals carrying a sinus stenosis-associated deranged intracranial pressure control, which also shares the ability to trigger a migraine attack at relatively low trigemino-vascular activation threshold.…”
Section: Is Migraine a Primary Or A Secondary Condition?mentioning
confidence: 99%
“…The prevalence of cutaneous allodynia in patients with migraine is rather high, estimated to be between 40–70%. The presence of allodynia is a marker of central sensitization in migraineurs and is associated with an elevated risk for chronification [ 152 ]. In addition, with its dual origin from two distinct arms of diseases (i.e., chronic pain syndromes and primary headache disorders), CM is a highly prevalent condition, having a great socio-economic impact and posing an individual burden.…”
Section: Discussionmentioning
confidence: 99%